Challenges in Law Enforcement Against Corporate Tax Crimes: Evaluation of Global Instruments - Rendi Risandy; Ani Purwati (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Economic globalization has increasingly complicated efforts to enforce laws against multinational corporate tax crimes, particularly those involving cross-border tax avoidance and evasion. This study seeks to address two main research questions: first, what are the legal barriers to implementing global instruments such as the OECD Base Erosion and Profit Shifting (BEPS) project and the Financial Action Task Force (FATF) Recommendations in Indonesia? Second, what institutional obstacles hinder their enforcement? Employing a normative juridical method through an extensive literature review, this study identifies several challenges. On the legal side, Indonesia faces disharmony between domestic regulations and international standards, creating gaps that can be exploited by corporations. Weak sanctions and persistent legal loopholes further undermine the effectiveness of enforcement. On the institutional side, barriers include limited human resource capacity, insufficient expertise in international tax matters, and weak inter-agency coordination. Additionally, inadequate technological infrastructure limits the ability of authorities to monitor and analyze complex cross-border transactions effectively. These factors collectively reduce Indonesia’s capacity to prevent and address multinational tax avoidance schemes. To overcome these challenges, the study recommends aligning national tax laws more closely with international frameworks, strengthening sanction regimes to deter violations, and closing loopholes that are routinely manipulated by corporations. Moreover, it emphasizes the need to enhance institutional capacity through specialized training, improved inter-agency cooperation, and the adoption of advanced digital technologies to support enforcement. By addressing these barriers holistically, Indonesia can improve its effectiveness in combating corporate tax crimes in the context of global economic integration.